2009
DOI: 10.1158/1535-7163.mct-09-0160
|View full text |Cite
|
Sign up to set email alerts
|

NVP-BEZ235, a novel dual phosphatidylinositol 3-kinase/mammalian target of rapamycin inhibitor, elicits multifaceted antitumor activities in human gliomas

Abstract: Aberrant genetic alternations in human gliomas, such as amplification of epidermal growth factor receptor, mutation and/or deletion of tumor suppressor gene PTEN, and mutations of PIK3CA, contribute to constitutive activation of the phosphatidylinositol 3-kinase (PI3K) pathway. We investigated the potential antitumor activity of NVP-BEZ235, which is a novel dual PI3K/mammalian target of rapamycin (mTOR) inhibitor in gliomas. The compound suppressed glioma cell proliferation with IC 50 values in the low nanomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
153
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 26 publications
14
153
1
1
Order By: Relevance
“…NVP-BEZ235 is a pan-PI3K inhibitor that acts against all of the isoforms of PI3K and PI3K mutants. Previous studies have demonstrated the efficacy of NVP-BEZ235 as an antitumor agent in vitro and in vivo in glioblastoma, multiple myeloma, melanoma, lymphoma, www.nature.com/aps Pal I et al Acta Pharmacologica Sinica npg sarcoma, breast, lung, and ovarian cancer models [84][85][86][87][88][89][90][91][92][93] . In the case of colon cancer, NVP-BEZ23 decreases cellular proliferation and causes sustained inhibition of mTORC1 and mTORC2 with a transient PI3K blockade with no subsequent effect on apoptosis either in vitro or in vivo in a GEM model.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…NVP-BEZ235 is a pan-PI3K inhibitor that acts against all of the isoforms of PI3K and PI3K mutants. Previous studies have demonstrated the efficacy of NVP-BEZ235 as an antitumor agent in vitro and in vivo in glioblastoma, multiple myeloma, melanoma, lymphoma, www.nature.com/aps Pal I et al Acta Pharmacologica Sinica npg sarcoma, breast, lung, and ovarian cancer models [84][85][86][87][88][89][90][91][92][93] . In the case of colon cancer, NVP-BEZ23 decreases cellular proliferation and causes sustained inhibition of mTORC1 and mTORC2 with a transient PI3K blockade with no subsequent effect on apoptosis either in vitro or in vivo in a GEM model.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…All these inhibitors are under investigation for treatment of glioblastoma (18)(19)(20). We have used the orthotopic U87 brain tumor model to evaluate the antitumor efficacy of the inhibitors and further investigated ZSTK474, being the PI3K inhibitor with the most favorable brain penetration, in a more clinically relevant transgenic glioblastoma model (21).…”
Section: Introductionmentioning
confidence: 99%
“…NVP-BEZ235, a novel dual PI3K/mTOR inhibitor, showed a dramatic effect on gliomas in various laboratory-based testing approaches. NVP-BEZ235 antagonizes the PI3K/mTOR signaling pathway and induces cell-cycle arrest, autophagy, and downregulation of vascular endothelial growth factor in glioma cells [17] . NVP-BEZ235 is also an effective radiosensitizer that inhibits ataxia telangiectasia mutated ( ATM ) and DNA-PK catalytic subunits ( DNAPKcs ), arrests cell cycle, and induces apoptosis [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%